The future of stellar occultations by distant solar system bodies: Perspectives from the Gaia astrometry and the deep sky surveys. (May 2018) - Camargo, J.I.B.; Desmars, J.; Braga-Ribas, F.; Vieira-Martins, R.; Assafin, M.; Sicardy, B.; Bérard, D.; Benedetti-Rossi, G.
Abstract: Distant objects in the solar system are crucial to better understand the history and evolution of its outskirts. The stellar occultation technique allows the determination of their sizes and shapes with kilometric accuracy, a detailed investigation of their immediate vicinities, as well as the detection of tenuous atmospheres. The prediction of such events is a key point in this study, and yet accurate enough predictions are available to a handful of objects only. In this work, we briefly discuss the dramatic impact that both the astrometry from the Gaia space mission and the deep sky surveys – the Large Synoptic Survey Telescope in particular – will have on the prediction of stellar occultations and how they may influence the future of the study of distant small solar system bodies through this technique. Abstract : Gaia and deep surveys foster the study of the outer solar system from occultations. Milli-arcsecond accurate predictions of stellar occultations are now achievable. Weighing schemes in orbit determination play an important role.